Neonatal morbidity after induction versus expectant monitoring in intrauterine growth restriction at term. (18th April 2012) - Boers, KE; Thornton, JG; Scherjon, SA
Abstract : Objective: In our recent DIGITAT trial, (Disproportionate Intrauterine Growth Intervention Trial at Term) there was no difference in the primary neonatal composite outcome, but after allocation to induction neonates were admitted more frequently to an intermediate type of fetal care. We wished to test whether this was a protocol driven effect, or based on a true difference in neonatal morbidity, by comparing neonatal morbidity directly using the morbidity assessment index for newborns (MAIN) score. Study design: We used data from the DIGITAT-trial, a randomised study comparing induction and expectant management in term IUGR. In each of the neonates, we calculated the MAIN score, a validated outcome scale. Results: There were no significant differences in mean MAIN scores (46 induction vs. 52 expectant; mean difference -6; 95% CI [-24;12]), nor in MAIN morbidity categories. Neonatal admissions were lower after 38 weeks gestational age compared to 36 and 37 weeks in both groups. Conclusions: The lack of difference in neonatal morbidity in women with IUGR at term is reassuring for the induction of labour policy, and suggests that the apparent increase in intermediate level admission was protocol driven rather than a marker of real morbidity. The observation that neonatal admissions are lowest after 38 weeks supports delaying an induction policy to pre-empt possible stillbirth until this gestation. Trial Register number: ISRCTN10363217